초음파와 극초단파를 이용한 송이버섯의 추출법과 다당체에 관한 연구 - 유승현(Seung Hyun Yu); 정명수(Myong Soo Chong); 김혜자(Hae Ja Kim); 이기남(Ki Nam Lee) (동의생리병리학회지, 2007)
In order to optimize the extract condition and improve physiological activity of the extract form Tricholoma matsutake, experiments related to extraction methods, totale yield, content of total soluble polysaccharide, SOD-like activity, total polyphenol amount, and volatile flavor compound and the others were carried out, results were obtained as following: Compare with traditional hydrothermal extraction method (Hot water extraction : HWEW), it illustrates that the low temperature extraction method which combines a supersonic waves and microwave (Supersonic microwave extraction : SMEW) causes of increasing the total yield, total soluble polysaccharide. As to the anti-oxident effect, SMEW method leds to increasing of the SOD-like activity, total polyphenol amount as well. Also, cytotoxic effect and growth inhibitory effect against cancer cell line are much higher in SMEW method than HWEW method, especially SMEW5 extracts treated by supersonic 15 min. and microwave 120W, 3 min. and 2 times. The main volatile flavor compound and infinitesimal volatile flavor compound both increase significantly by SMEW method. It is concluded the main components of the volatile flavor compounds extracted from Tricholoma matsutake are 1-octen-3-0l, Methyl cinnamate, 2-octeno1 et al. alcohol typies. Consequently, SMEW5 method is considered as the most effective one for anti-oxidant and is prior to any other methods. And the optimun conditions of this method are : supersonic waves (supersonic, 25KHz, 50W) 15 minutes, microwave spectroscopy (microwave, 2,450MHz, 120W) 3 minutes, and every treatment is performed once followed twice repeats.